Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
[tex]General\ formula\ for\ line:\\\\y=ax+b,\ where\ a-gradient\\\\y=6x+b\\\\Substitute\ point\ (-1,6):\\\\6=6\cdot(-1)+b\\6=-6+b\\b=6+6\\b=12\\\\y=6x+12\\\\Substitute\ point\ (7,a)\\\\a=6\cdot7+12\\a=42+12=54[/tex]
We can also see it this way:
Noting that point in the form (x, y)
(-1, 6) and (7, a) . x1 = -1, y1 = 6, x2 = 7, y2 = a
Gradient , m = (y2- y1) / (x2 - x1). m =6.
Substituting:
6 = (a - 6) / (7 - -1)
6 = (a -6) / (7+1)
6 = (a -6) /8 Cross Multiplying
48 = a -6.
48 +6 = a.
54 = a.
Therefore a = 54.
I hope this helps.
Noting that point in the form (x, y)
(-1, 6) and (7, a) . x1 = -1, y1 = 6, x2 = 7, y2 = a
Gradient , m = (y2- y1) / (x2 - x1). m =6.
Substituting:
6 = (a - 6) / (7 - -1)
6 = (a -6) / (7+1)
6 = (a -6) /8 Cross Multiplying
48 = a -6.
48 +6 = a.
54 = a.
Therefore a = 54.
I hope this helps.
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.